Application of Pectin Coating Containing Essential Oil for Increasing Quality of Strawberry Fruit - Abdi, Soma; Roein, Zeynab; Erfanimoghadam, Javad; Aziznia, Somayeh (Journal of Postharvest Technology, 2017)
Edible coatings and essential oils increase quality of product during storage due to their ability to control gas and moisture exchange and  antimicrobial properties, respectively. The study was carried out using a factorial design with two factors include time (4 level) and treatment (6  level) in a completely randomized design with three replication. To evaluate the effect of coating on shelf life and quality of strawberry fruits, 2  concentrations (0.5 and 1%) of lemon and orange peel essential oil along with pectin was used. After fruit immersion in coating solution for 1  min, fruits were storage at temperature of 5 0C and relative humidity of 75±1 % evaluate shelf life, biochemical characteristics such as total  soluble solids, total acidity, pH, antioxidant activity and weight loss. According to the results, with an increase in storage time, all evaluated  characteristics showed an upward trend. The highest shelf life (24.23 days) observed in pectin with 1% lemon essential with a 12day of  increase observed compared to the control. The results show that the control treatment accounted for the highest amount of soluble solids and  total acidity during the period of storage. Moreover, the pectin enriched in two concentrations of lemon essence (0.5% and 1%) decreased  significantly fruit weight loss. At the mid time of storage period, there were no significant differences in soluble solids between pectin enriched  in 0.5 and 1% orange essence (6.48 and 6.53% respectively). In addition, during the period of storage, the pectin enriched in 1% orange  essence showed less weight loss and soluble solids in comparison to the control. At the end of storage time, pectin with lemon essence  illustrated the higher antioxidant activity than pectin with orange essence treatment. At this time, the highest amount of total acidity and the  lowest amount of pH (0.75% and 6.76, respectively) observed in the pectin enriched in 1% lemon essence. In general, the results showed that  1% lemon essential oil had higher effects on preserving fruit quality and appearance than orange essential oil and essential-free pectin  treatments. Therefore, use of essential oils for their antimicrobial properties coupled with edible coatings can be used as an effective treatment  for strawberry fruit post-harvest technology.
Keywords: Essential oils; Postharvest; Shelf life; Strawberry; Total soluble solids